Special paperThe impact of geographical distances to coronary angiography laboratories on the patient evaluation pathways in patients with suspected coronary artery disease. Results from a population-based study in Hungary - Nemes, Attila; Király, Ferenc; Vassányi, István; Kósa, István (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : Coronary artery disease (CAD) has been a leading cause of death in the western world for the last few decades, despite significant improvements in treatment and management. Diagnostic algorithms for the evaluation of patients with suspected CAD are based on available guidelines. Aim : To evaluate the impact of geographical distances to coronary angiography laboratories on the patient evaluation pathways in patients with suspected CAD, from a population-based study in Hungary. Material and methods : Depersonalised data of 29,202 patients identified by their pseudo-social security number were analysed. All patients underwent coronary angiography as an initial direct invasive investigation (DI) following an at least half-year-long stable period between 1 January 2004 and 31 December 2008. Results : One hundred and thirty-five dominant primary cardiology centres (PCC) have been identified, from which 85 proved to have sample size more than 100 DIs in tertiary cardiology centres (TCC). The frequency of DIs showed a close correlation with PCC-TCC distances (r = –0.44, p < 0.001). A negative correlation could be demonstrated between the age of patients and PCC-TCC distances (r = –0.45, p < 0.001). Without significant change in the absolute mortality, the relative mortality increased with the increase in PCC-TCC distance (r = 0.25, p < 0.05). Conclusions : The PCC-TCC distance has an important effect on patient pathways in subjects with suspected CAD.